Sistem Pendukung Keputusan Penilaian Pelanggan Menggunakan Metode TOPSIS - Salim, Richie; Elizabeth, Triana (Jurnal Teknologi Sistem Informasi, 2023)
Information technology is growing and becoming one of the factors supporting success in running a business. PT. Primakarsa Niaga Indonesia operates in the electronic distributor area located in Jalan Colonel H Burlian, Palembang. The company performs a customer assessment specifically for store customers every two times a year aiming for which customers would eventually qualify for the reward. There are barriers when the company will make a decision to determine the best customer, i.e. difficulty in determining which customer to choose because at the time of observation the customer buys a lot of goods but at the moment of payment is not on time. To facilitate this assessment, a decision-supporting system was developed using the TOPSIS method with a number of criteria determined by the company, methodologies RUP, use case, class diagram, and activity diagram. As for the tools used for the creation of this application is visual studio code as a code editor using the programming language PHP, the database used is MySQL database, and will use the Laravel framework. The result of this system is that it can help the company in making decisions faster to choose customers